Joint cluster reconstructions - combing free-form lensing and X-rays - Huber, Korbinian; Tchernin, Céline; Merten, Julian; Hilbert, Stefan; Bartelmann, Matthias (Astronomy and astrophysics, 2019)
Galaxy clusters provide a multitude of observational data across wavelengths, and their structure and morphology are of considerable interest in cosmology as well as astrophysics.Aims. We develop a framework that allows the combination of lensing and non-lensing observations in a free-form and mesh-free approach to infer the projected mass distribution of individual galaxy clusters. This method can be used to test common assumptions on the morphology of clusters in parametric models.Methods. We make use of the lensing reconstruction code SAWLENS2, and expand its capabilities by incorporating an estimate of the projected gravitational potential based on X-ray data that are deprojected using the local Richardson-Lucy method and used to infer the Newtonian potential of the cluster. We discuss how potentially arising numerical artefacts can be treated.Results. We demonstrate the feasibility of our method on a simplified mock Navarro-Frenk-White (NFW) halo and on a cluster from a realistic hydrodynamical simulation. We show how the combination of X-ray and weak lensing data can affect a free-form reconstruction, improving the accuracy in the central region in some cases by a factor of two.
Gesehen am 28.04.2020